An Alternative Paradigm of Sustainable Environmental Development in Developing Countries: Amartya Sen’s Ideas and Their Implications for Indonesia - Daud Duli; Julia Roses Kadja Dahi; Vinsensius Lau; Lorensius R. L. Dhae; Nur Iam Ri'a; Kobun, Aloysius L.L.; Tuani, Armi D. (Jurnal Kebijakan Pembangunan, 2025)
The dominant development paradigm in developing countries has long been shaped by conventional that emphasize Gross Domestic Product (GDP) growth and market efficiency, often neglecting the dimensions of ecological justice and citizens’ substantive freedoms. This article examines the capability approach developed by Amartya Sen as a conceptual alternative that places human freedom and environmental quality as integral components of development. Employing a conceptual research method grounded in recent literature, this study proposes an integration of the capability framework and ecological justice as both ethical and practical foundations for sustainable development in Indonesia. The findings demonstrate that Amartya Sen’s capability approach functions as a strategic development model for achieving sustainable environmental development by reorienting policy priorities from more economic efficiency toward the systematic expansion of ecological and human capabilities, particularly among vulnerable groups. The application of this model requires the formulation of development indicators, the strengthening of inclusive public participation, and the protection of community-managed territories as core instruments of a long-term, equitable, and sustainable environmental development strategy.